Slowly Decaying Radial Solutions of an Elliptic Equation with Subcritical and Supercritical Exponents - Guerra-Benavente, I (Springer New York LLC, 2016)
We study radial solutions of the problem Δu + up + uq=0, u > in ℝN, where N ≥ 3 and (Formula Presented.). We show that if p is close to N/(N-2), q is close to (N +2)/(N-2), and a certain relation holds between them, then the problem has slowly decaying solutions. © 2016, Hebrew University Magnes Press.